KONFLIK ANTARA KELOMPOK TANI DENGAN PENGURUS KUD PRIMA SEHATI (STUDI KASUS : PADA LOKASI DESA KENEGERIAN CENGAR KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI) - Iya Nevila Hawari; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted in Kenegerian Cengar Village, Kuantan MudikSubdistrict, Kuantan Singingi Regency with the aim to obtain information aboutthe conflict between Farmer Group and KUD Prima Sehati. The several problemsin this research are (1) How are the forms of conflict between members of FarmerGroup and KUD Prima Sehati? (2) How is the process of resolving the conflictbetween the Farmer Group and the KUD Prima Sehati? The title of this study is